Perilaku Harian Udang Air Tawar Macrobrachium terhadap Perbedaan Arus pada Pengkondisian Laboratorium: Daily Behavior of Freshwater Prawn Macrobrachium pilimanus (De Man, 1879) in Response to Water Current Under Laboratory Conditions - Rachman, Muhammad Dhiya'ur; Pratiwi, Intan Ratu; Yodhy, Lintang; Raffiudin, Rika (Jurnal Sumberdaya Hayati, 2025)
Macrobrachium pilimanus is a type of freshwater prawn commonly found in Indonesian waters. This species is reported to have abbreviated larval development (ALD), and its life cycle is greatly influenced by the conditions of their environment, including the water currents. This study examined the relationship between water currents and the daily behavior of the M. pilimanus freshwater prawn. We observed the behavioral pattern using the scan sampling method on six individuals from two treatments (strong current and slow current) over 64 hours, with observations taken every 60 minutes. Our results showed a dominant behavior of M. pilimanus hiding in places with strong currents and high ingestion behavior. In contrast, the prawns that were not exposed to water currents predominantly showed partially inactive behavior.